Two sources of low-development traps from a human capital perspective - Santos, Maria Emma (2018)
This paper analyzes two possible sources of low-development traps related to human capital accumulation. The first one comes from a mismatch between the skills workers have acquired through their formal education and the skills demanded by some non-innovative firms in the labor market. The second one comes from segmentation in the educational system, such that the children of better educated parents receive a higher quality education than the children of less educated parents. Two different models are presented in which each of these sources cause, correspondingly, dual economies and low-development traps.